Supportive policy environment on informal seed systems leads to increased use of local climate-resilient varieties - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Bioversity International has established community seedbanks to enable farmers to have easy access to diverse, good quality seeds. Seed banks play a vital role in ensuring seed security and improving farmers’ access to seeds, conserving agricultural biodiversity and the associated traditional knowledge, providing options for adapting to climate change.